Flow simulation analysis of maju cable tunnel ventilation system / Ahmad Hafiz Jafarul Tarek - Ahmad Hafiz, Jafarul Tarek (2019)
One of Maju Utility Tunnel functions is to accommodate the cable buried underground. Hence, tunnel ventilation is required to prevent the cable from malfunctioning due to lack of air throughout the tunnel. This research report shows the types of tunnel ventilation (natural vs mechanical ventilation) where the velocity variation plays its role to achieve thermal comfort for workers. Natural ventilation cools down the tunnel using the surrounding air (Case 1), and mechanical ventilation setup requires auxiliary components such as inlet pump and exhaust system for cooling down (Case 2 and Case 3). High velocity shows improvement for temperature distribution. This is proven by CFD analysis as it can achieve the lowest temperature, which is 33.8˚C. At the same time, we determine Air change per hour (ACPH) of the tunnel. ACPH indicates how much air can enter and exit the tunnel, which means the higher the velocity, the higher the exchanged air is. The range between 20 - 40 of ACPH is used as a benchmark on ideal condition. The volume and CFM are also set as the parameters for ACPH calculations. The difference between Case 2 and Case 3 is the addition of the exhaust system. The capability of the mechanical ventilation pumping power to cool down the tunnel is determined via formula calculation.